1992
DOI: 10.1152/ajprenal.1992.263.5.f841
|View full text |Cite
|
Sign up to set email alerts
|

Folate transport and binding by cultured human proximal tubule cells

Abstract: Because mechanisms for the renal regulation of folate excretion are poorly understood, a cell culture system representative of the human proximal tubule (HPT) was used for studies of renal folate transport. After confluent cultures of HPT cells were incubated with 3H-labeled folic acid (PteGlu), binding to the apical membrane was determined by an acid removal procedure, and transport was subsequently measured in solubilized cells. Although PteGlu binding was almost all specific (suppressed by excess unlabeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
19
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 0 publications
4
19
0
Order By: Relevance
“…Injection of 3 H-MTHF also confirms the important role of folbp1 for renal tubular reabsorption, showing increased urinary excretion and decreased renal accumulation in folbp1Ϫ/Ϫ. These findings, establishing for the first time in an in vivo model a direct role for folbp1 in epithelia folate uptake, confirms the hypotheses raised by the identification of FR in the kidney proximal tubule and by observations on folate transport in the kidney and in cultured kidney cells (14,20,32,33). In addition, folbp1 is heavily expressed in other absorptive epithelia, including the rodent yolk sac (34) and choroid plexus (15).…”
Section: Discussionsupporting
confidence: 77%
“…Injection of 3 H-MTHF also confirms the important role of folbp1 for renal tubular reabsorption, showing increased urinary excretion and decreased renal accumulation in folbp1Ϫ/Ϫ. These findings, establishing for the first time in an in vivo model a direct role for folbp1 in epithelia folate uptake, confirms the hypotheses raised by the identification of FR in the kidney proximal tubule and by observations on folate transport in the kidney and in cultured kidney cells (14,20,32,33). In addition, folbp1 is heavily expressed in other absorptive epithelia, including the rodent yolk sac (34) and choroid plexus (15).…”
Section: Discussionsupporting
confidence: 77%
“…28 The binding of folate to the folate receptor occurs at a relatively high affinity with half maximal binding as high as 12 nM in human proximal tubule cells, making it ideal for pharmacological targeting. 25,26,29 In this study, we synthesized a novel folate-antioxidant conjugate to selectively target the kidney, to enhance localized superoxide scavenging, and to prevent the development of ARF while avoiding the associated side effects of systemic antioxidant therapy. [16][17][18]30,31 We hypothesize that the tempol-folate conjugate selectively targets the renal proximal tubule and protects from ischemic injury by way of scavenging reactive oxygen species, therefore preventing the cascade of events resulting in tubular dysfunction and ARF ( Figure 1A).…”
mentioning
confidence: 99%
“…In general, folate-based radiopharmaceuticals show a high radiotracer accumulation in the kidneys due to a physiologic folate receptor expression in proximal tubule cells (16). Recently, Müller et al reported a favorable effect of the antifolate pemetrexed on kidney and tumor uptake (17,18); thus, the high radioactivity accumulation and the potential risk of damage to the kidneys may no longer be an issue.…”
mentioning
confidence: 99%